Pelaksnaan Pembelajaran Melalui Permainan KOBAR (Kotak Baca Bergambar) Untuk Meningkatkan kemampuan membaca anak Di PAUD Dellia Creative School - Ina Julianti; Rita Prima Bendriyanti; Ranny Fitria Imran; E Yuliana (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to improve reading skills of early childhood through kobargame (Illustrated ReadingBox) at PAUD Dellia Creative School, KalicodeStreet, Padang Harapan, and Bengkulu City.This type of research is classroom action research. The subjects in this study were children aged 5-6 years consisting of 12 children. The data collection technique is done by using observation and documentation.The results of the studyafter implementing activities using KOBAR (Illustrated ReadingBox), namely in the first cycle of the first meeting 31% and at the second meeting increased to 50% with 7 children starting to develop and 5 children developing as expected. Whereas,in the second cycle of the first meeting got 75% results and at the second meeting got 100% results with the criteria that the childrenwas developing very well. The results obtained from the percentage of everything from the overall research were 88% with Very Good Criteria